Tributação internacional e preços de transferência: as ações 8, 9 e 10 do projeto BEPS como instrumentos de limitação do planejamento tributário abusivo e de combate à erosão da base tributária - Pinheiro, Ivanovick Feitosa Dias (2023)
The exercise of fiscal sovereignty can affect facts abroad. This eventually generates unwanted double taxation. To eliminate it, States legislate internally and sign international agreements, many under the influence of the OECD model convention. In this context - and in the exercise of economic freedom - some companies adopt tax planning aimed at legitimately reducing taxes. However, some organizations commit abuses, such as treaty shopping. Tax planning, in these situations, can lead to tax avoidance with the consequent erosion of the tax base. This study aims to analyze the issue of transfer pricing - through the perspective parameterized by actions 8, 9 and 10 of the BEPS project - as a mechanism to combat the abuse of fiscal planning and the erosion of the tax base. The context of the analysis focuses on themes essential to its understanding, such as: international taxation, arm's length, transfer pricing, associated companies, abuse of rights, intangibles, risks and value. The method adopted was the deductive hypothetical. The study showed that tax sovereignties must act cooperatively and combat double taxation, as well as abuse of freedom in tax planning. Income transfers cannot be used for tax manipulation, under penalty of impacting the development of the world economy. In addition, it was shown that transfer pricing - notably from the perspective of actions 8, 9 and 10 of the BEPS project - are an adequate mechanism to combat tax avoidance and erosion of the tax base resulting from improper tax planning.